Cultural Imprint of Doumen Ancient Street - Study on the Integration of Tradition and Innovation in the Design of Tourist Souvenirs - Yuan, Xiaopeng; Puntien, Pisit (Journal of Roi Kaensarn Academi, 2024)
The rich historical culture and folk customs of Doumen Ancient Street are losing their vitality due to globalization and modernization. This study proposes innovative cultural product designs to revitalize tourism and preserve its heritage.This study aims to design and express Doumen Ancient Street cultural products in different forms, and constantly summarize and them into tourist souvenirs with clear characteristics. Through in-depth analysis of the historical buildings, intangible cultural heritage, and local folk customs of Doumen Ancient Street, this study proposes a series of innovative souvenir design solutions. These solutions are not only aimed at enhancing the cultural experience of tourists, but also committed to promoting the development of cultural tourism in Doumen Ancient Street. The study uses field visits, interviews, and questionnaires to collect first-hand information on the cultural identity of Doumen Ancient Street, and based on this, designs tourist souvenirs with clear characteristics. Finally, through user experience evaluation, the effectiveness of these souvenirs in conveying the cultural value of Doumen Ancient Street was verified, providing new ideas and practical solutions for the cultural communication and tourism development of Doumen Ancient Street.